Release thresholds for moss spores: the importance of turbulence and sporophyte length. (21st March 2014) - Johansson, Victor; Lönnell, Niklas; Sundberg, Sebastian; Hylander, Kristoffer; Jongejans, Eelke
Summary Adequately describing the dispersal mechanisms of a species is important for understanding and predicting its distribution dynamics in space and time. For wind‐dispersed species, the transportation of airborne propagules is comparatively well studied, while the mechanisms triggering propagule release are poorly understood, especially for cryptogams. We investigated the effect of wind speed and turbulence on spore release in the moss Atrichum undulatum in a wind tunnel. Specifically, we measured the amount of spores released from sporophytes when exposed to different wind speeds, in high and low turbulence, using a particle counter. We also related spore release to variation in vibrations of the sporophyte and investigated how the vibrations were affected by wind speed, turbulence and sporophyte length (here including capsule, seta and the top part of the shoot). We show that in high turbulence, the amount of spores released increased with increasing wind speed, while in low turbulence, it did not, within the wind speed range 0.8–4.3 m s−1. However, there was a threshold in wind speed (˜2.5–3 m s−1) before large amounts of spores started to be released in turbulent flow, which coincided with incipient vibrations of the sporophyte. Thresholds in wind variation, rather than average wind speed, seemed to initiate sporophyte vibrations. The vibration threshold increased with decreasing sporophyte length. The deposition of spores near the source decreased with increasing wind variation during the time of their release, based on simulated spore deposition from another study of moss dispersal. Synthesis. We suggest that vibration of moss sporophytes is an important mechanism to regulate spore release and that turbulence and sporophyte length regulate the onset of sporophyte vibration. Spore release thresholds affect dispersal distances and have implications for our understanding and predictions of species distribution patterns, population dynamics and persistence. The mechanisms of this phase of the dispersal process are also important to explore for other species, as there may be a substantial variation depending on the species' different traits.